(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
Emotional Intelligence, a term developed over time to indicate one’s ability to understand their personal emotions and the emotions of others around them. Trait Emotional Intelligence is a term coined by Petrides in order to redefine the works of literature on the topic and put them together into a scale that could be examined through questionnaires. This study implemented the TEIQue-SF which is a shorter form of the full questionnaire itself with 30 items, 4 factors and a completion time of around 5 minutes. The goal was to investigate the correlation between the 4 factors that the questionnaire offers (well-being, self-control, emotionality and sociability) and the proficiency level of TEFL students in Syria. The study included 283 participants (75 males and 208 females). The participants are from various proficiency levels ranging from A1 to B2 according to CEFR and the results of a placement test conducted prior to the questionnaire. The data was collected from one private language center in Damascus- Syria. The research concluded that there is a weak positive relation between learners’ proficiency level and two of the factors (r=.143, sig=.017 for self-control and r=.147, sig=.013 for sociability). Also, the global score had an (r=.154, sig=.010). This indicates that there is a weak statistical correlation between TEFL learners’ language proficiency. Recommendations have been suggested for further research and practical aspects.